Pengaruh Gaya Hidup dan Motivasi Belanja Hedonis Terhadap Minat Beli Pengguna Aplikasi Shopee di Kota Banjarmasin - Mildawati Mildawati; Purboyo Purboyo; Teguh Wicaksono (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to examine the influence of lifestyle and hedonic shopping motivation on the buying interest of Shopee application users in Banjarmasin City.The research method used is quantitative method. The number of samples used by 106 respondents was taken by purposive sampling. Data collection using online questionnaires. Data analysis methods use descriptive statistics, instrumental testing, multiple linear analysis and hypothesis testing. This test uses the help of SPSS 26 statistical software.The results of this study show that lifestyle variables (X1) have a significant positive influence on buying interest variables. The hedonic shopping motivation variable (X2) has a positive influence on the buying interest variable. Based on simultaneous testing, lifestyle variables (X1) and hedonic shopping motivation variables (X2) on the buying interest of shopee application users together have a significant influence.